Library and Information Studies Press and Freedom of Expression - Samek, Toni (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Analysis of the literature of library and information studies (LIS) reveals that6 the role of Practicum in LIS education has come full circle. Today, as in the early days of the profession, Practicum is a core element of LIS education, for both pedagogical and practical reasons. Practicum links theory and practice and extends learning options. Many students enroll in Practicum to gain work experience to.